2013
DOI: 10.1111/ane.12194
|View full text |Cite
|
Sign up to set email alerts
|

Mood and coping in clinically isolated syndrome and multiple sclerosis

Abstract: This study highlights transient mood alterations and an improving of adaptive coping over a period of time in patients with CIS and RRMS. Similar emotional reactions and coping in clinical subgroups suggest that these factors are independent from the type of information provided during the communication of the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…This finding may underline the need for the clinician to consider that moderate/severe disability is also associated with higher trait anxiety. These patients may be unable to cope with stressful life events, and therefore they may need to be included in a non‐pharmacological intervention to get a psychological support and help them to use active copying strategies . Moreover, the lack of association between anxiety levels and MS duration suggested that anxiety can occur throughout the disease course and that anxiety levels should be assessed even at early phases of MS.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may underline the need for the clinician to consider that moderate/severe disability is also associated with higher trait anxiety. These patients may be unable to cope with stressful life events, and therefore they may need to be included in a non‐pharmacological intervention to get a psychological support and help them to use active copying strategies . Moreover, the lack of association between anxiety levels and MS duration suggested that anxiety can occur throughout the disease course and that anxiety levels should be assessed even at early phases of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression are known to be common among individuals with MS (da Silva, Vilhena, & Lopes, ; Bianchi, De Giglio, & Prosperini, ). In earlier studies, both conditions were found to be important factors contributing to poor sleep quality in MS patients (Vitková et al., ; Boe Lunde et al., ), although we found no studies presenting data about their impact on sleep quality in women and men with MS. Observations from previous studies conducted among the general population and other chronic conditions showed depression and/or anxiety to be specific contributors of poor sleep in women (Mallampalli & Carter, ; Palagini, Tani, & Bruno, ; Castro‐Sanchez, Mataran‐Penarrocha, & Lara‐Palomo, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, quantitative studies might fail to do so, as they might, in such cases, be incapable of creating rich data, which is often the result of deep understanding of the phenomenon. On the other hand, coping with the disease is a multidimensional concept, 16 which could vary depending on the context and Soci-cultural factors as well as being affected by the differences within and across individuals. 17 Furthermore, such issues might be coupled with certain problems which are peculiar to the Iranian context to further complicate the matter; Iranian patients with MS may not have easy access to the required medications, may lack support in terms of rehabilitation, treatment costs, etc., which are specific to the area of Iran.…”
Section: Introductionmentioning
confidence: 99%